2017
DOI: 10.1177/2054358117693355
|View full text |Cite
|
Sign up to set email alerts
|

Total Kidney Volume as a Biomarker of Disease Progression in Autosomal Dominant Polycystic Kidney Disease

Abstract: Purpose of review:Autosomal dominant polycystic kidney disease (ADPKD) is an inherited disorder characterized by the formation of kidney cysts and kidney enlargement, which progresses to kidney failure by the fifth to seventh decade of life in a majority of patients. Disease progression is evaluated primarily through serum creatinine and estimated glomerular filtration rate (eGFR) measurements; however, it is known that serum creatinine and eGFR values typically do not change until the fourth or fifth decade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…Despite this, validation exercises found that in the absence of TKV data, disease progression predicted by the ADPKD-OM remained plausible over a range of baseline values. As the prognostic value of TKV growth in ADPKD patients is increasingly recognised and advocated [ 8 , 38 ], the adoption of this measure in routine clinical practice will only enhance predictions of disease progression generated by the ADPKD-OM.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, validation exercises found that in the absence of TKV data, disease progression predicted by the ADPKD-OM remained plausible over a range of baseline values. As the prognostic value of TKV growth in ADPKD patients is increasingly recognised and advocated [ 8 , 38 ], the adoption of this measure in routine clinical practice will only enhance predictions of disease progression generated by the ADPKD-OM.…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal dominant polycystic kidney (ADPK) disease is one of the most common hereditary disorders and is characterized by progressive cyst formation and the enlargement of the kidney and other organs (e.g., liver, pancreas, and spleen) (1). Ultimately, gradually growing cysts lead to kidney failure by the fifth of sixth decade of life (2).…”
Section: Introductionmentioning
confidence: 99%
“…32 Of interest, these methods show more accuracy on CT in comparison to MRI due to slice thickness and utilisation of the Cavalieri method; however, this would not be feasible due to the chronic nature of ADPKD and serial imaging requirements over decades and the radiation hazards carried by CT. MRI is therefore the most accurate method practically applicable to imaging requests, with the time requirement being the biggest factor to impact on MRI reporting adding on average at least 30 additional minutes to produce accurate reproducibility. 33 We must evaluate the additional value this carries in enhancing the radiological report, considering volume estimation is useful in such patients particularly around decision making on Tolvaptan commencement. 34 A request from the renal physician specifying volume measurement after patient selection would lend huge help in guiding radiologists to prioritise the imaging requiring additional reporting time, with a pathway similar to vasculature evaluation for potential kidney donorsthese can then be assigned subspecialists within Radiology to take on responsibility for TKV estimation reporting in addition to producing a standard MRI report.…”
Section: Discussionmentioning
confidence: 99%